2019
DOI: 10.1186/s13104-019-4639-8
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of obstetric danger signs and its associated factors among pregnant women in Angolela Tera District, Northern Ethiopia

Abstract: Objective Knowledge of danger signs of obstetric complications is the first essential step in accepting appropriate and timely referral to maternal and newborn care units. The objective of this study was to assess the knowledge of obstetric danger signs and associated factors among pregnant women in Angolela Tera district, Northern Ethiopia. A community based cross sectional study was conducted among 563 pregnant women who were selected by multi-stage cluster sampling technique. Data were colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
70
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(83 citation statements)
references
References 19 publications
(31 reference statements)
9
70
3
1
Order By: Relevance
“…Regardless, it was found that women who had a good BPCR had an improved level of maternal healthcare utilization than those who were not. A prior arrangement made on part of the mother such as identi cation of the birth attendant and facility gives expectant mothers an impulse to utilize delivery and postnatal care (23,24). Our nding agrees with previous studies that reported BPCR predicted better use of maternal healthcare services (14,25).…”
Section: Discussionsupporting
confidence: 90%
“…Regardless, it was found that women who had a good BPCR had an improved level of maternal healthcare utilization than those who were not. A prior arrangement made on part of the mother such as identi cation of the birth attendant and facility gives expectant mothers an impulse to utilize delivery and postnatal care (23,24). Our nding agrees with previous studies that reported BPCR predicted better use of maternal healthcare services (14,25).…”
Section: Discussionsupporting
confidence: 90%
“…This finding is inconsistent with other studies which showed that urban residence had a significant association with knowledge of ODS. (19,(23)(24)(25) This may be because 82.3% of study participants in this study were rural.…”
Section: Discussionmentioning
confidence: 94%
“…This study showed that there was a statistically significant association between women's knowledge of ODS and multiparity, which is in line with previous studies. (25,27) This may be because multiparous women have more experience with pregnancy and labor than others due to their multiple deliveries. In this study, respondents who had more antenatal visits were more knowledgeable than those who had less number and this is consistent with other studies.…”
Section: Discussionmentioning
confidence: 99%
“…Studies elsewhere reported increased knowledge with more ANC visits [15] and utilizing ANC services [18]. Health education increases awareness of danger signs [17,24] and is reported to have doubled the odds of knowing about danger signs [9].…”
Section: Factors Associated With Levels Of Knowledgementioning
confidence: 99%